Why is the West Dying? The age of reason sources of the antipopulation trends. Patterns of consumption, self-realization and salvation in worldliness - Hennig, Konrad (Myths and Stereotypes in the Collective Representations, 2019)
The western societies are shrinking and getting older. These demographical processes have roots in civilizational solutions explored and imposed by the revolutionaries of Enlightenment. The cultural patterns created by the 18th century philosophers are still and continuously actual. The set of modern and postmodern ideas including consumerism, self-realization and salvation during mortal life are the core reasons of demographical problems of western societies. People aren’t eager to have families and children. They perceive the traditional way of life as a personal sacrifice. They feel a strong need to devote themselves to their own desires and joys. People live their lives as they were to be the last generation of their nations and seem not to be worried or even concerned by that fact.